2014
DOI: 10.1186/s13099-014-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Phase-variable restriction/modification systems are required for Helicobacter pylori colonization

Abstract: BackgroundOne mechanism utilized by bacterial pathogens for host adaptation and immune evasion is the generation of phenotypic diversity by the phasevarion that results from the differential expression of a suite of genes regulated by the activity of a phase-variable methyltransferase within a restriction modification (RM) system. Phasevarions are active in Helicobacter pylori, however there have been no studies investigating the significance of phase-variable RM systems on host colonization.MethodsTwo mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…However, in contrast to the ModH5 phasevarion, flgE is positively regulated by the ModH1 OFF-phase. In line with these observations of ModH-mediated gene regulation, a role for ModH phase switching in H. pylori colonization has been implicated by the findings of a recent mouse model study 20 . Despite the predictive transcriptional evidence, the phenotypic role of ModH phase switching in H. pylori motility had not been examined.…”
Section: Introductionmentioning
confidence: 62%
“…However, in contrast to the ModH5 phasevarion, flgE is positively regulated by the ModH1 OFF-phase. In line with these observations of ModH-mediated gene regulation, a role for ModH phase switching in H. pylori colonization has been implicated by the findings of a recent mouse model study 20 . Despite the predictive transcriptional evidence, the phenotypic role of ModH phase switching in H. pylori motility had not been examined.…”
Section: Introductionmentioning
confidence: 62%
“…Molecular investigations of phase-variable R-M genes have also been carried out on the Hp strain OND79, confirming their presence in six out of nine of the mentioned Hp strains, and further functional analyses were conducted. All three types of R-M system genes were reported to be equally distributed in the studied strain, while the functional analysis showed that the mod gene is a main player in colonization and in the regulation of different gene expressions ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have focused on inversion, improvements in targeted methylation analysis (59) could enable the study of cisacting sites at the P-and S-pilus promoters (49). Furthermore, PacBio sequencing can detect transposition, short sequence repeats, and slipped-strand mispairing; these capabilities may be useful for studying phase variation of other nonplus structures, such as flagella and lipoproteins (49), or restriction-modification systems, which impact phage defense and global gene expression (60)(61)(62). Additionally, with appropriate screen design, unbiased discovery of trans-acting factors for phase variation may be feasible.…”
Section: Discussionmentioning
confidence: 99%